KOMPOSISI KIMIA MINYAK ATSIRI PADA BEBERAPA TIPE DAUN TEMBAKAU (Nicotiana tabaccum L.) - Elda Nurnasari; Subiyakto Subiyakto (BERITA BIOLOGI, 2011)
Steam distilation of tobacco (Nicotiana tabaccum L) from 4 different area, Madura (1160 gram), Temanggung (2000 gram),Bondowoso (3528 gram), and Blitar (950 gram) yielded 2,67x10-2 %, 6,93x10-2 %, 0,8428%, and 0,0632 % essensial oil respectively.The oils then analyzed using GC-MS methods. The results identified 30 components from the Madura’s tobacco, 11 components from the Temanggung’s tobacco, 67 components from the Bondowoso’s tobacco, and 20 components from the Blitar’s tobacco.The major essential oil compounds was neophytadien.